Monetary policy and the financial system - Horvitz, Paul M. (Englewood Cliffs, N.J.: Prentice-Hall, 1963)
The emphasis in this book is on monetary policy which is the principal end to study of money and banking. Monetary theory is discussed in sufficient depth to enable students and readers grasp the theoretical basis of issues in monetary economics and finance.
Includes index.
usc 22/06/2017
Loans
Keywords: Monetary policy; Finance; United States